2020
DOI: 10.1681/asn.2020040424
|View full text |Cite
|
Sign up to set email alerts
|

TrkC Is Essential for Nephron Function and Trans-Activates Igf1R Signaling

Abstract: BackgroundInjury to kidney podocytes often results in chronic glomerular disease and consecutive nephron malfunction. For most glomerular diseases, targeted therapies are lacking. Thus, it is important to identify novel signaling pathways contributing to glomerular disease. Neurotrophic tyrosine kinase receptor 3 (TrkC) is expressed in podocytes and the protein transmits signals to the podocyte actin cytoskeleton.MethodsNephron-specific TrkC knockout (TrkC-KO) and nephron-specific TrkC-overexpressing (TrkC-OE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…Our results, obtained by qPCR and ISH, show that nt3/trkC is the most expressed in different regions, including the hematopoietic cells, similarly to the mammalian kidney [62,63]. Previous observations in rats and humans highlighted that nt3 and trkC mRNA levels were elevated in the glomerular tissue, and this signaling could be involved in the regulation of renal tubule transport [64][65][66]. In detail, Lepa and colleagues, using a mammal animal model, confirmed that nephron-specific TrkC knockout (TrkC-KO) and TrkC-overexpressing (TrkC-OE) mice presented enlarged glomeruli with mesangial proliferation, podocyte loss during aging, basement membrane thickening, and albuminuria.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our results, obtained by qPCR and ISH, show that nt3/trkC is the most expressed in different regions, including the hematopoietic cells, similarly to the mammalian kidney [62,63]. Previous observations in rats and humans highlighted that nt3 and trkC mRNA levels were elevated in the glomerular tissue, and this signaling could be involved in the regulation of renal tubule transport [64][65][66]. In detail, Lepa and colleagues, using a mammal animal model, confirmed that nephron-specific TrkC knockout (TrkC-KO) and TrkC-overexpressing (TrkC-OE) mice presented enlarged glomeruli with mesangial proliferation, podocyte loss during aging, basement membrane thickening, and albuminuria.…”
Section: Discussionsupporting
confidence: 56%
“…In detail, Lepa and colleagues, using a mammal animal model, confirmed that nephron-specific TrkC knockout (TrkC-KO) and TrkC-overexpressing (TrkC-OE) mice presented enlarged glomeruli with mesangial proliferation, podocyte loss during aging, basement membrane thickening, and albuminuria. They also showed that NT3-dependent TrkC activation in cultured podocytes and overexpression of TrkC in the nephron in mice lead to the phosphorylation of the activating tyrosine residues of the Igf1R [66].…”
Section: Discussionmentioning
confidence: 96%
“…The level of PI3K correlated with phosphorylation of IGF1R, which con rms activation of the pathway during IRI. It was shown that dysregulation of IGF signalling played a role in several kidney diseases, such as proteinuric CKD and polycystic kidneys [24]. Downregulating the IGF1R/PI3K pathway limited loss of podocytes in mice model of diabetic nephropathy [25].…”
Section: Discussionmentioning
confidence: 99%